2020
DOI: 10.3389/fonc.2019.01500
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Radiation Pneumonitis With Dose Distribution: A Convolutional Neural Network (CNN) Based Model

Abstract: Radiation pneumonitis (RP) is one of the major side effects of thoracic radiotherapy. The aim of this study is to build a dose distribution based prediction model, and investigate the correlation of RP incidence and high-order features of dose distribution. A convolution 3D (C3D) neural network was used to construct the prediction model. The C3D network was pre-trained for action recognition. The dose distribution was used as input of the prediction model. With the C3D network, the convolution operation was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 28 publications
(32 reference statements)
3
42
0
Order By: Relevance
“…Moreover, PR curves were calculated with emphasis on the incidence of RP in the minor class. 30 For predicting RP after VMAT, Liang et al conducted a PR curve analysis using a convolution 3D neural network 33 ; the result was consistent with our dosiomic approach. In our study, the PR-AUC significantly improved when switching from the DVI models to the dosiomic and hybrid models.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, PR curves were calculated with emphasis on the incidence of RP in the minor class. 30 For predicting RP after VMAT, Liang et al conducted a PR curve analysis using a convolution 3D neural network 33 ; the result was consistent with our dosiomic approach. In our study, the PR-AUC significantly improved when switching from the DVI models to the dosiomic and hybrid models.…”
Section: Discussionsupporting
confidence: 75%
“…The existence of a strict relationship between the dose distribution, a change of CT texture features before and after RT, and the risk of RILI development was firstly demonstrated by Cunliffe et al ( 66 ). Recently, this dosiomic approach was replicated through a convolutional deep-neural network analysis ( 67 , 68 ) in a cohort of 70 NSCLC patients treated with volumetric modulated arc therapy (VMAT), providing a high discriminative power (AUC of 0.84) over standard logistic regression models for the prediction of radiation pneumonitis. Taking into account the much less clinically relevant impact of radiation pneumonitis in the context of stereotactic body RT, limited data are available ( 69 , 70 ) in this context in comparison to conventionally-fractionated regimens.…”
Section: Thoracic Radiotherapy: Lungmentioning
confidence: 99%
“…The results showed that CNN performed better than the traditional model, with an AUC of 0.842. 59 Lee et al applied ML and bioinformatics tools to genome-wide data to predict and explain the late genitourinary system toxicity in prostate cancer patients after radiotherapy. 60 DL’s prediction of the efficacy and side effects of radiotherapy was able to screen out the possible beneficiaries of radiotherapy in clinical work and to prepare for possible side effects.…”
Section: Methodsmentioning
confidence: 99%